Social determinants of health that permeate the mental suffering of children on the french-brazilian border - Nádia Cristine Coelho Eugenio Pedrosa; Carolina Almeida de Oliveira; Maria Izabel Tentes Côrtes; Renan Alves Silva; Marina Nolli Bittencourt; Jordânia Vieira Silva (Associação Brasileira de Enfermagem, 2021)
ABSTRACT Objectives: to understand the determinants involved in the mental suffering of schoolchildren on the French-Brazilian border. Methods: a qualitative study was conducted with children from 6 to 12 years of age from four State schools in the municipality of Oiapoque, located on the French-Brazilian border. The data were obtained through interviews, analyzed by the IRAMUTEQ software, and interpreted in the light of the Dahlgren and Whitehead's social determinants of health model. Results: data indicate that the mental suffering experienced by children, especially characterized by anxious symptoms, such as concern of becoming fat and worries, were permeated by social situations that children went through daily, such as family abandonment, domestic violence, and bullying. Final Considerations: social determinants can be predictors of mental suffering in children, especially in environments of extreme vulnerability, such as the border, in a context of financial difficulties, domestic violence, and absence of parenting.